The productivity effects of multiple pay incentives. (November 2017) - Pendleton, Andrew; Robinson, Andrew
Drawing on recent incentive theory and the growing use of multiple incentives by firms, this article examines the effects of combining incentives on workplace labour productivity. Utilizing data from the British Workplace Employment Relations Survey, the article explores whether multiple incentives are more effective than single incentives. It is found that the productivity effects of individualized incentives are enhanced by profit sharing though not by collective payment by result schemes (PBR). Profit sharing also enhances the effect of collective PBR, and it is found that two group incentives are more effective than a single individual incentive. However there are limits on the number of incentive schemes that can be combined effectively. The effects of mixed incentives tend to be greater in workplaces with worker discretion and task variety, thereby providing support for a contingency perspective.